Small bowel adenocarcinoma of the jejunum detected by double contrast enhanced ultrasound: a case report of a novel ultrasound modality - Wu, Shuang; Yu, Huizhen; Liu, Ying; Zhou, Hong; Zhou, Yang (Frontiers in Oncology, 2024)
Background Small Bowel Adenocarcinoma (SBA) is rare, occult and life-threatening malignancy in digestive system. Given low incidence and nonspecific symptoms, SBA is frequently detected in later stages. Double contrast enhanced ultrasound (DCEUS) is an innovative imaging technique applied to visualize the gastrointestinal tract, merging intravenous contrast-enhanced ultrasound with oral contrast-enhanced ultrasound. In this case, DCEUS was utilized and successfully detected an SBA of the jejunum. Case presentation A Chinese woman, aged 64, sought consultation in the gastroenterology department at our hospital, reporting symptoms of abdominal pain. Three months before entering the hospital, she underwent gastroscopy and colonoscopy which suggested chronic gastritis, and she was treated with oral drugs. However, her symptoms were not relieved, and even worsened. To further investigate, DCEUS was performed. The oral contrast agent dilated the luminal space of the upper gastrointestinal tract, resolving the hindrance caused by gas in the gastrointestinal tract and creating an acoustic window for scanning. Through this acoustic window, oral agent contrast-enhanced ultrasound (OA-CEUS) revealed a localized thickening of jejunal intestinal wall measuring 4x3 cm. Following intravenous injection of ultrasound contrast agent, the jejunal lesion exhibited faster enhancement and heterogeneous hyper-enhancement. Finally, the patient underwent jejunal tumor resection. Pathological examination revealed a jejunal adenocarcinoma. Conclusion The timely diagnosis of SBA can be challenging. DCEUS may have the potential to contribute to diagnosis and detailed evaluation of SBA, particularly in cases involving jejunum. Further researches are needed to fully explore the benefits of DCEUS in the standard diagnostic approach for small bowel diseases.